The dark days of Hamburger Halpin - Berk, Josh. (New York : Ember, 2011)
When Will Halpin transfers from his all-deaf school into a mainstream Pennsylvania high school, he faces discrimination and bullying, but still manages to solve a mystery surrounding the death of a football player in his class.
Originally published: New York : Alfred. A. Knopf, 2010.
Accelerated Reader AR
Keywords: Deaf people -- Juvenile fiction; People with disabilities -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Bullying -- Juvenile fiction; Murder -- Juvenile fiction; Detective and mystery stories; Deaf people -- Fiction; People with disabilities -- Fiction; High schools -- Fiction; Schools -- Fiction; Bullies -- Fiction; Murder -- Fiction; Mystery and detective stories